Impact of rock salt creep law choice on subsidence calculations for hydrocarbon reservoirs overlain by evaporite caprocks. Issue 6 (29th June 2016) - Marketos, G.; Spiers, C. J.; Govers, R.
Abstract: Accurate forward modeling of surface subsidence above producing hydrocarbons reservoirs requires an understanding of the mechanisms determining how ground deformation and subsidence evolve. Here we focus entirely on rock salt, which overlies a large number of reservoirs worldwide, and specifically on the role of creep of rock salt caprocks in response to production‐induced differential stresses. We start by discussing available rock salt creep flow laws. We then present the subsidence evolution above an axisymmetric finite element representation of a generic reservoir that extends over a few kilometers and explore the effects of rock salt flow law choice on the subsidence response. We find that if rock salt creep is linear, as appropriate for steady state flow by pressure solution, the subsidence response to any pressure reduction history contains two distinct components, one that leads to the subsidence bowl becoming narrower and deeper and one that leads to subsidence rebound and becomes dominant at later stages. This subsidence rebound becomes inhibited if rock salt deforms purely through steady state power law creep at low stresses. We also show that an approximate representation of transient creep leads to relatively small differences in subsidence predictions. Most importantly, the results confirm that rock salt flow must be modeled accurately if good subsidence predictions are required. However, in practice, large uncertainties exist in the creep behavior of rock salt, especially at low stresses. These are a consequence of the spatial variability of rock salt physical properties, which is practically impossible to constrain. A conclusion therefore is that modelers can only resort to calculating bounds for the subsidence evolution above producing rock salt‐capped reservoirs. Key Points: A review of available rock salt creep laws is presented as there is no consensus on flow laws in the literature Finite element results for rock salt‐capped reservoirs are used to discuss mechanisms by which creep leads to time‐varying subsidence Results from finite element simulations that test the effects of changing the rock salt flow constitutive model on subsidence are presented